2014
DOI: 10.4103/0974-2077.129981
|View full text |Cite
|
Sign up to set email alerts
|

The management of helical rim keloids with excision, split thickness skin graft and intralesional triamcinolone acetonide

Abstract: Keloids of the helical rim are disfiguring. A cosmetically acceptable reconstruction is difficult especially in moderate to large sized lesions because the helical rim is a 3-dimensional structure with curved and thin cartilage. We report our experience in the management of moderate (4-10 cm) and large (>10 cm) helical rim keloids in five patients. Six helical rim keloids were reconstructed. There were four moderate (4-10 cm) and two large (>10 cm) helical rim keloids. Four were on the right helix and two on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…As suggested by previous studies, huge helical defects following surgical excision of keloids can be a great reconstructive challenge to many plastic surgeons. For this reason, Burm and Hansen reported their successful experiences using full‐thickness skin grafting with marginal de‐epithelialization to reconstruct the defect following the excision of helical rim keloids , while Rasheed and Malachy reported their split‐thickness skin grafting experiences as full‐thickness skin grafting is generally considered too unreliable over a poorly vascularised bed such as a helical defect with exposed cartilage . However, as already suggested in our previous study, using skin grafts and neglecting the initial step on the reconstructive ladder can expose patients to more risk than necessary.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As suggested by previous studies, huge helical defects following surgical excision of keloids can be a great reconstructive challenge to many plastic surgeons. For this reason, Burm and Hansen reported their successful experiences using full‐thickness skin grafting with marginal de‐epithelialization to reconstruct the defect following the excision of helical rim keloids , while Rasheed and Malachy reported their split‐thickness skin grafting experiences as full‐thickness skin grafting is generally considered too unreliable over a poorly vascularised bed such as a helical defect with exposed cartilage . However, as already suggested in our previous study, using skin grafts and neglecting the initial step on the reconstructive ladder can expose patients to more risk than necessary.…”
Section: Discussionmentioning
confidence: 82%
“…Sand et al reported a case of a large keloid on the helical rim that was successfully treated with surgery, intralesional injection of a combination of 0·5 ml triamcinolonacetonid and 2% scandicain and a custom‐designed silicon pressure clip . Rasheed and Malachy reported their experience of six helical rim keloids in five patients using surgical excision followed by split‐thickness skin grafting and postoperative steroid injection therapy at 2 weeks, postoperatively . Burm and Hansen demonstrated their successful experience in seven helical keloids in seven patients using surgical excision followed by full‐thickness skin grafting that was followed by multivitamins' administration and topical creams and sunscreen application .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, closure can be achieved with simple sutures after the excision of small and single keloids, while wounds in patients with huge keloids cannot be closed with low‐tension primary sutures. In such cases, reconstructive techniques that limit dermal tension, such as z‐plasties, skin grafts, and skin flaps, should be used to achieve cosmetic and functional results 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…In such cases, reconstructive techniques that limit dermal tension, such as z-plasties, skin grafts, and skin flaps, should be used to achieve cosmetic and functional results. [11][12][13][14] However, outcomes for patients with huge keloids who underwent excision and reconstruction combined with radiotherapy were still unclear, especially the impact of radiotherapy on reconstructive methods. Therefore, the present study aimed to evaluate the efficacy and safety of surgical excision and reconstruction combined with radiotherapy for huge keloids in a single center with 13 years of experience.…”
mentioning
confidence: 99%